Szkodliwe interakcje wewnątrzrodzinne w kontekście cywilizacyjnych przemian - Mastalski, Janusz (Studia Pastoralne, 2026)
A contemporary family bears the consequences of the universal affirmation of individualism, laxism and consumerism. Consequently, alternatives for the home are boldly searched for, demolishing at the same time the traditional social order. The author discusses the most disturbing interfamilial phenomena associated with relationships. These are: the tendencies to compete; aggressive interactions; lack of desired mutual cross-references because of absence; individualism; superficiality of interactions between members of the household; inadequate communication in the family house; the growing manipulation in mutual relations; interactions resulting from co-addiction; “insulation relationships”; mediatization of mutual interpersonal relationships; interactions resulting from the permutations of roles in the family and toxic relationships as a result of atrophy of the family bonds. The article concludes with a proposal of a remedial program.